2007
DOI: 10.1038/sj.ejcn.1602890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucromalt on postprandial responses in human subjects

Abstract: Backgroud/Objective: To compare postprandial responses elicited by sucromalt, a nutritive sweetener produced by treating a blend of sucrose and corn syrup with an enzyme from Leuconostoc mesenteroides, with those after 42% of high-fructose corn syrup (HFCS), and to see if the reduced responses after sucromalt could be accounted for by carbohydrate malabsorption. Subject and Methods: Three experiments were performed in separate groups of normal subjects studied after overnight fasts using double-blind, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
6
23
0
2
Order By: Relevance
“…These substances contained primarily a-(1,3) and a-(1,6) linkages. These findings are consistent with previous reports on Sucromalt, which is composed of similar linkages and is hydrolysed to glucose in in vitro and human models (Grysman et al 2008;Lee et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These substances contained primarily a-(1,3) and a-(1,6) linkages. These findings are consistent with previous reports on Sucromalt, which is composed of similar linkages and is hydrolysed to glucose in in vitro and human models (Grysman et al 2008;Lee et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the substances that were used as highly digestible controls in the in vitro and animal experiments, maltodextrin is formed from units of glucose with a-(1,4) bonds (Eliasson 2006), whereas PSF (purified Sucromalt fraction) has an average DP of 10 and comprises glucoses that are linked by alternating a-(1,3) and a-(1,6) linkages, except for the terminal glucose molecules, which are joined by an a-(1,4) bond (Grysman et al 2008;Lee et al 2016). PDX, the low-digestible control, has an average DP of 12, a molecular weight of approximately 2 Â 10 3 g/mol, and all various combinations of aand b-linked (1,2), (1,3), (1,4) and (1,6) glycosidic linkages, of which (1,6) linkages predominate (Lahtinen et al 2010), but it is not easily digested due to its highly branched polymeric structure (Craig et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Los carbohidratos digeridos lentamente pueden viajar más abajo en el intestino delgado antes de ser absorbidos y estimular un incremento plasmático tardío del GLP-1 (25). Tal es el caso de la sucromaltosa (análogo natural de la sacarosa, de menor impacto glucémico) (18,25), con incremento sostenido del GLP-1 durante cuatro horas postingesta de 50/80 g, lo que confirma su lenta absorción (25). Esto sugiere que la cantidad/calidad de los CHO podría mejorar la función de las células beta del DM2 en tiempo prolongado (2).…”
Section: Discussionunclassified
“…It has also been reported that alternan oligosaccharides derived from alternanase activity are used as low-glycemic sweeteners. Some studies state that these oligosaccharides are potential prebiotics (Leathers, Hayman, and Côt e 1997), however in vivo trials in humans showed that they are slowly but fully digestible by human digestive enzymes in the gastrointestinal track (2008, Grysman, Carlson, andWolever 2008;Vanschoonbeek et al 2009). A recent study on a-glucan oligomers containing (a1!6) and (a1!3) linkages with DP ranging from 3-12, showed similar glucose and insulin response curves as the dextrose control in humans.…”
Section: Alternan and Alternan-oligosaccharidesmentioning
confidence: 99%